Food retail profits, competition, and the Great Recession. Issue 3 (27th May 2022) - Cleary, Rebecca; Chenarides, Lauren
Abstract: We investigate the competitive effects of entry in the food retail sector in nonmetropolitan counties in the United States from 1998 to 2014. We pay particular attention to the period that covers the Great Recession, which disrupted market structure across a number of industries. Using a county‐level panel dataset, we use a seminal entry model to infer the local competitive effects of entry in the food retail sector. We estimate entry thresholds over time, which we then use to describe the rate of decline in profit margins following subsequent entry via entry threshold ratios. We find that food retail firms required a smaller market size to break even during the Great Recession, perhaps pointing to higher profits, as consumers shifted purchases to food‐at‐home. This effect is short‐lived for all but a single firm. The market threshold required to support a single food retail firm remains low throughout the post‐recession recovery period. We also find that the second firm may not decrease profit margins, but that competition increases meaningfully with the third and fourth entrants. The increased competition during the Great Recession also appears to have persisted into the recovery period. [EconLit Citations: L18; Q18].